Effectiveness of Chest Physiotherapy with Thoracic Expansion Exercise (TEE) in Pneumonia Patients - Ahmad Wibowo, David; Andari; Pramusinta, Linda (STIKES Telogorejo Semarang, 2022)
Background: Pneumonia is an infectious lung disease that can affect anyone, such as children, adolescents, young adults, and the elderly. One of the appropriate treatments to overcome the problem of pneumonia is physiotherapy using Chest Physiotherapy and Thoracic Expansion Exercises (TEE). Objective: The aim of this study was to evaluate the effect of chest physiotherapy and thoracic expansion exercise in pneumonia patients Method and Materials: In this study, a literature review was used to obtain information regarding the effect of Chest Physiotherapy and Thoracic Expansion Exercise (TEE) on patients with pneumonia. A thorough study was conducted on 2 topics: (1) Pneumonia (2) Chest physiotherapy and Thoracic Expansion Exercise (TEE) pneumonia. The inclusion criteria were (1) the sample was a patient suffering from pneumonia (2) in a pneumonia patient the therapeutic modalities were chest physiotherapy and Thoracic Expansion Exercise (TEE). Effective search was deliberately limited to English, with interesting studies in pneumonia patients and published in the last 9 years. Literature research was conducted on the PubMed and Google Scholar electronic databases, for the period between January 2013 and January 2022. Result: Meta-analysis of 3 articles showed that after the intervention, the P value was very significant.Conclusion: The provision of physiotherapy interventions in the form of Chest Physiotherapy and Thoracic Expansion Exercise (TEE), can have a significant effect on pneumonia patients.